Gender- based Variations in Perception of Flood Impacts -A Micro Study - Panigrahi, Neeladri; Satpathy, Bineeta; Ashok Kumar Singh, (Indian Journal of Extension Education, 2023)
An attempt to understand the perception of flood impacts through a gender lens was executed in 2022 in the purposively selected Darbangha district of Bihar as it tops the list of the districts most severely affected by flood in the state. Data from 120 farmers were collected through a focused group discussion and an interview schedule developed specifically for the study.  The findings revealed that the maximum percentage of farmers had a medium perception regarding the impact of floods. Variations were seen in the perception of the socio-economic and psychological impact of flood with women perceiving slightly higher than men whereas the opposite was seen for the perception of the environmental impact of the flood where men perceived slightly higher than women. Factors like age, household headship, social participation, decision-making, education, and family size significantly and positively affected the perception women and men had on the impact of the flood. The findings provide an in-depth understanding of the perception of the impact of floods by men and women farmers in the study area which would help the extension agencies and policymakers to plan and design locale-specific preparedness.